Hardware qualification for scientific ballooning missions. Issue 6 (15th March 2023) - Pahler, A.; Böttger, J.; Bougueroua, S.; Emberger, M.; Janson, O.; Jokschas, T.; Keilig, T.; Klinkner, S.; Krabbe, A.; Lengowski, M.; Maier, P.; Taheran, M.
Highlights: The ESBO initiative aims at simplifying the access to ballooning for scientists. Environmental conditions dictate the qualification tests for balloon missions. While similar to space conditions, there are also significant differences. Space standards can be used for stratospheric ballooning, but have to be modified. The ESBO qualification approach for balloon-borne hardware is based on ECSS standards. Abstract: The European Stratospheric Balloon Observatory (ESBO) initiative aims at simplifying the access to stratospheric balloon missions. We plan to provide platforms and support with instrument design in order to support scientists. During the design process, the inevitable question of qualification for the harsh flight conditions arises. Unfortunately, there is no existing standard for qualification of stratospheric ballooning hardware. Thus, we developed a qualification procedure for use within ESBO and similar projects. In this paper, we present our analysis of the environmental conditions in the stratosphere. While conditions at typical balloon float altitudes are similar to the space environment, there are also some relevant differences. For example, the thermal environment is dominated by radiation and thermal conduction, but the remaining atmosphere still supports a certain amount of convection. The remaining atmospheric pressure in the stratosphere also leads to reduced arcing distances. Vibrational loads are far less than for space missions, but quasi-static or shock loads may occur. The criticality of radiation increases with mission duration. Based on the environmental conditions, we present the qualification procedures for ESBO, which are based on the European Cooperation for Space Standardization (ECSS) standards for space systems. Overtesting against too high requirements leads to overengineering, driving mission cost and mitigating the advantages of balloons over space missions. Therefore, we modified the ECSS standards to fit typical scientific ballooning missions over several days at altitudes up to 40 km. Furthermore, we analyzed design rules for space systems with regard to their relevance for scientific ballooning, including material and component selection. We present the experience from the hardware qualification process for the ESBO prototype STUDIO (Stratospheric UV Demonstrator of an Imaging Observatory). Even though boundary conditions are different for each individual mission, we aimed for a broader approach: We investigated more general requirements for scientific ballooning missions to support future flights.